Evidence of local adaptation to aridity but not nitrogen deposition in invasive annuals - Valliere, Justin M.; Hernández, Mayra J.; Sharifi, M. Rasoul; Rundel, Philip W. (Ecology (Durham), 2025)
Rapid adaptation of traits and trait plasticity may contribute to plant invasiveness and confer fitness advantages in novel environments resulting from global change. The importance of trait differentiation in invasive plant populations is well recognized, particularly in response to climate. However, it is largely unknown how invasive plant populations will respond evolutionarily to atmospheric nitrogen (N) deposition resulting from air pollution, which is a major contributor to invasion success in many ecosystems. Using a common garden experiment, a widely used method for testing local adaptation, we assessed potential differences in plant functional traits and nitrogen plasticity across populations of two widespread invasive annuals from sites spanning a range of N deposition and aridity throughout southern California. These species exhibited clear population‐level differences in traits and N responses, but these were unrelated to N deposition. Instead, we detected significant relationships between several traits and aridity, and populations from more arid sites exhibited reduced N plasticity for multiple traits. Multivariate plasticity indices also showed a strong negative relationship with aridity across populations for both species. However, trait responses to N addition also appeared to be influenced by species' drought‐coping strategies. In Bromus diandrus, a drought‐escaping early‐season annual grass, populations from less arid sites showed increased plasticity in shoot growth and more rapid flowering in response to N addition. In contrast, Centaurea melitensis, a drought‐tolerant late‐season forb, showed climate‐driven shifts in biomass allocation in response to N; populations from more arid sites invested more in roots, while populations from less arid sites allocated more to leaves. These contrasting N responses strongly suggest distinct growth strategies and ecophysiological trade‐offs shaped by adaptation to local climate conditions. While elevated N availability may indeed promote invasion, climate stress might exert an overriding influence on local adaptation of plant invaders in dryland ecosystems subject to N deposition.